Three-Dimensional Reconstruction of Blood Vessels of the Human Retina by Fractal Interpolation - Guedri, Hichem (J Nanotechnol Eng Med, 2015)
In this work, data from two-dimensional (2D) images of the human retina were taken as a case study. First, the characteristic data points had been removed using the Douglas–Peucker (DP) method, and subsequently, more data points were added using random fractal interpolation approach, to reconstruct a three-dimensional (3D) model of the blood vessel. By visualizing the result, we can see that all the small blood vessels in the human retina are more visible and detailed. This algorithm of 3D reconstruction has the advantage of being fast with calculation time less than 40 s and also can reduce the 3D image storage level on a disk with a reduction ratio between 78% and 96.65%.